2016 AIChE Spring Meeting & 12th Global Congress on Process Safety : 5th Process Safety Management Mentoring (PSM2) Forum (Center for Chemical Process Safety/AIChE, 2016)
The Mission and Purpose of the Process Safety Management Mentoring (PSM2) Forum at the Global Congress of Process Safety is to provide those new to the field with the basics of Process Safety Management (PSM). This track is aimed at young engineers, professionals new to the field, and those interested in strengthening the fundamentals of PSM. The content of the track is balanced between tutorial material, lessons learned, and panel discussions. The framework for the track relies upon the CCPS's 20 elements of risk-based process safety. The introductory and basic content of the PSM2 track is complemented by the advanced topics and discussions in the other three symposia of the Global Congress.
Prepared for Presentation at American Institute of Chemical Engineers 2016 Spring Meeting 12th Global Congress on Process Safety Houston, Texas April 11-23, 2016.
Keywords: Chemical process control.; Chemical plants -- Safety measures.; elektronické knihy; electronic books